Tensile Strength and Failure Characteristics of Common Roof Truss Joints - Abdul Rahman, Mahadzir (2002)
Timber joints have always been the weak link in timber construction. Although the load carrying capacity of the timber structure is greater than the applied load, the structural system can fail if the joints are weak. Finger jointing of short off-cut timbers for structural purposes like lightweight roof trusses is an economical method to minimise wastage and to increase recovery rate. The objective of this research was to evaluate the strength and failure characteristics of truss joints made from solid and finger jointed kempas (Koompassia malaccensis) with metal plate connectors. This research assessed the strength properties of truss joints comprising solid and finger-jointed kempas which were jointed with nail plate connectors. The influence of the location of finger joints in the joint system on both the strength and failure characteristics were also studied. Eight joint types, each having ten replications were tested for joint strengths and failure modes. The type of jOint were solid butt-joint (S8), solid T -joint (ST), finger jointed butt-joint type 1 (FB1), finger jointed butt-joint type 2 (FB2) and finger jOinted butt-joint type 3 (FB3), finger jointed T -joint type 1 (FT1), finger jointed T -joint type 2 (FT2) and finger jointed T-joint type 3 (FT3).